2020
DOI: 10.1039/c9gc02657f
|View full text |Cite
|
Sign up to set email alerts
|

The clean preparation of multisubstituted pyrroles under metal- and solvent-free conditions

Abstract: A practical method for the clean preparation of multisubstituted pyrroles via an iodine-catalyzed multicomponent reaction under metal- and solvent-free conditions was developed. In the gram-scale synthesis, the pyrroles can be easily collected through simple extraction.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
12
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 72 publications
(12 citation statements)
references
References 86 publications
0
12
0
Order By: Relevance
“…Amines and their derivatives are important bulk chemicals and industrial intermediates for pharmaceuticals, agrochemicals, dyes, etc. Catalytic hydrogenation of nitro compounds using hydrogen as a reducing agent provides an essential pathway toward producing amines. Such catalytic reduction is receiving increasing attention, because it is eco-friendly, economical, and generates few byproducts. Noble-metal-based catalysts are the most common catalysts used in hydrogenation of nitro compounds, because of their high catalytic activity. However, besides their high price, noble-metal-based catalysts are prone to be poisoned by even a trace amount of CO or H 2 S, which often come from either the production of H 2 or the hydrogenation products. In addition, they often show poor hydrogenation selectivity. For example, it is possible for other unsaturated functional groups, such as −CC–, −CHO, −CC–, and −CN, to be reduced in the hydrogenation of nitro groups as well. , Therefore, alternative catalysts that possess low cost, as well as high selectivity, and can resist the poisoning of CO or H 2 S, are commendably required for the hydrogenation of nitro compounds.…”
Section: Introductionmentioning
confidence: 99%
“…Amines and their derivatives are important bulk chemicals and industrial intermediates for pharmaceuticals, agrochemicals, dyes, etc. Catalytic hydrogenation of nitro compounds using hydrogen as a reducing agent provides an essential pathway toward producing amines. Such catalytic reduction is receiving increasing attention, because it is eco-friendly, economical, and generates few byproducts. Noble-metal-based catalysts are the most common catalysts used in hydrogenation of nitro compounds, because of their high catalytic activity. However, besides their high price, noble-metal-based catalysts are prone to be poisoned by even a trace amount of CO or H 2 S, which often come from either the production of H 2 or the hydrogenation products. In addition, they often show poor hydrogenation selectivity. For example, it is possible for other unsaturated functional groups, such as −CC–, −CHO, −CC–, and −CN, to be reduced in the hydrogenation of nitro groups as well. , Therefore, alternative catalysts that possess low cost, as well as high selectivity, and can resist the poisoning of CO or H 2 S, are commendably required for the hydrogenation of nitro compounds.…”
Section: Introductionmentioning
confidence: 99%
“…Very recently, Gui and co‐workers successfully developed a sustainable, green, metal‐ and solvent‐free synthesis of multisubstituted pyrroles via iodine catalyzed multicomponent reaction of equimolar amounts of alkynes, TMSCN and N,N ‐disubstituted formamides with high atom economy (Scheme 35). [90] Substrate scope was well investigated for alkynes and N,N ‐disubstituted formamides, and reported that the electron‐deficient and electron‐rich functional groups could tolerate the optimized reaction conditions to give excellent yields. The proposed synthetic protocol is highly sustainable and guided by 12 principles of green chemistry through the use of molecular iodine as a catalyst and performing the multicomponent reaction strategy under neat conditions.…”
Section: Miscellaneousmentioning
confidence: 99%
“…In order to meet the requirements of Green Chemistry, the development of an environment-friendly approach for organic synthesis has received considerable interest in recent years. In general, organic transformations are performed in toxic and volatile organic solvents, which are not only non-renewable fossil fuels but also have potential toxicity and risks. Therefore, great effort has been devoted to developing aqueous phase reactions for organic synthesis. In addition, as a renewable light energy, sunlight-induced photocatalytic reactions have become a green and simple strategy for organic transformation. On the other hand, the development of multicomponent transformations has attracted extensive interest because they provide a greater impact with substantial minimization of waste, labor, time, and cost relative to linear syntheses. Based on the urgent requirements of green synthesis and our research interests in developing green catalytic systems and C–H functionalization reactions, herein, we demonstrate a novel and green multicomponent transformation for the bifunctionalization of methyl ketones (Scheme b). In this transformation, ion-exchange resin Amberlyst 15 was used as the promising heterogeneous catalyst because of its recoverability and reusability. In addition, quinoxalinones were selected as one of the reactants because they widely exist in natural products, functional materials, and pharmaceuticals. In particular, 3-functionalized quinoxalinones are known for their superior chemical properties and outstanding biological activities, …”
Section: Introductionmentioning
confidence: 99%